2008
DOI: 10.1039/b805915b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and computational study of nitrogen-doped CeO2 nanoparticles with visible-light activity

Abstract: Nitrogen-doped CeO2 nanoparticles were synthesized through a wet-chemical route. Nitrogen has been successfully incorporated into CeO2 nanoparticles and the nitrogen-doping level was also successfully controlled. The optical properties due to the different N-doping levels in CeO2 nanoparticles were characterized by UV-Vis diffuse reflectance spectroscopy (DRS), which showed a visible-light absorbance shift. The resulting nanoparticles show enhanced visible-light sensitivity and photocatalytic activity compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
47
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 31 publications
0
47
1
3
Order By: Relevance
“…To the best of our knowledge, one of approaches is to develop CeO 2 based heterostructure semiconductor systems, such as TiO 2 @Pt@ . On the other hand, there have been modifications of CeO 2 by doping non-metallic species 13,14 and crystal facet engineering 15,16 . For instance, Zhu et al 13 reported the synthesis of N-doped CeO 2 nanoparticles with controllable doping levels at the nanoscale through a reliable wet chemical approach, showing enhanced visiblelight sensitivity and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, one of approaches is to develop CeO 2 based heterostructure semiconductor systems, such as TiO 2 @Pt@ . On the other hand, there have been modifications of CeO 2 by doping non-metallic species 13,14 and crystal facet engineering 15,16 . For instance, Zhu et al 13 reported the synthesis of N-doped CeO 2 nanoparticles with controllable doping levels at the nanoscale through a reliable wet chemical approach, showing enhanced visiblelight sensitivity and photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In particular, cerium oxide is one of the most promising materials, exhibiting excellent properties in gas sensors, 10 solar cells 11 and opticalbased non-volatile ash memory. These properties are dominated by their nanostructure and micro-morphology; therefore, various methods such as microwave-assisted thermal decomposition, 24 spray pyrolysis, 25 sol-gel processing 26 and hydrothermal methods 27 have been employed to prepare cerium oxide nanosheets, nanorods, nanowires and nanotubes. These properties are dominated by their nanostructure and micro-morphology; therefore, various methods such as microwave-assisted thermal decomposition, 24 spray pyrolysis, 25 sol-gel processing 26 and hydrothermal methods 27 have been employed to prepare cerium oxide nanosheets, nanorods, nanowires and nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective methods is doping. Zr- and La-doped CeO 2 have found their potential application in solar cell devices10, Mao et al demonstrated that N-doped CeO 2 shows a visible-light absorbance shift11.…”
mentioning
confidence: 99%